Retrograde ejaculation, painful ejaculation and hematospermia - Parnham, Arie (Transl Androl Urol, 2016)
Although there has been an increased interest on premature ejaculation in the recent years, our understanding regarding the disorders of retrograde ejaculation, painful ejaculation and hematospermia remain limited. All three of these conditions require a keen clinical acumen and willingness to engage in thinking outside of the standard established treatment paradigm. The development of novel investigational techniques and treatments has led to progress in the management of these conditions symptoms; however, the literature almost uniformly is limited to small series and rare randomised trials. Further investigation and randomised controlled trials are needed for progress in these often challenging cases.